Набоков vs Чернышевский: специфика осмысления «другого» в «Даре» В. В. Набокова - Осьмухина, Ольга Юрьевна; Osmukhina, Olga (Східноєвропейський національний університет імені Лесі Українки, 2017)
В статье рассматривается специфика восприятия творчества и образа Н. Чернышевского в романе В. Набокова «Дар». Впервые установлено, что «диалог на расстоянии» с творчеством Н. Чернышевского становится для В. Набокова попыткой понять «чужое» сознание, рассмотреть образ «другого» как «извне», так и «изнутри». Н. Чернышевский воспринимается как антидвойник главного героя. Осмысление его образа позволяет понять специфику соотношения автора / героя и поэтику текста в целостном единстве.The article discusses the specificity of the perception of N. Chernyshevsky creativity and image in the “Gift” of V. Nabokov. Once found that “dialogue at a distance” with creativity for Nabokov Chernyshevsky attempt to understand “alien” consciousness, consider the image of the “other” as “outside” and “inside”. Chernyshevsky is perceived as antidouble protagonist. Comprehension of its image allows to comprehend the specificity of the ratio of author / hero and the poetics of the text in the holistic oneness.
Nabokov vs Chernyshevsky: Specificity of Understanding “The Other” in the “Gift”of V. V. Nabokov
Keywords: Набоков; «другой»; герой; автор; двойник; антидвойник; Nabokov; the Other; hero; author; the double; hero, author, the double